Faktor-faktor Iklan yang Dapat Menarik Penonton Untuk Menonton Iklan Skip-Ads di Youtube Sampai Selesai - Anita Chrishanti Puteri Tito; Claudy Gabriella (Universitas Kristen Maranatha, 2019)
Along with the changing times, technology plays an important role in the marketing world. The increasing use of the internet has led to the shift of marketing using print media into online media. Deployment of marketing strategies can be found through various platforms such as websites and social media. One popular website is used as a means to market your product or service is YouTube. If someone is using YouTube certainly will often encounter many types of ads, but the most common and often comes up is true view in-stream ads that are usually will appear before the video starts. The ad will run for 5 seconds before it was finally has available options for in-skip. The problem that occurs is the lack of enthusiastic viewers to watch ads are marked with the number of viewers that will be to skip even before watching the commercials and this becomes a problem that hurt the company because it can not deliver the message properly. Therefore, researcher will find out the factors that can make viewers watch ads up to completion that are divided by age and gender. The method used in this study is exploratory research and based on the goals of this research it is an applied research because it will be used as a solution to solve the existing problems. The data collection will be done in two (2) methods: literature review and depth interview. The results showed the existence of some differences and some similarities between groups that will be presented in tabular form, analysed in qualitative method. Keyword: Online Advertising, YouTube, True View In-stream Ads, Exploratory Research, Depth Interview